A Metric Base Calaculation for Object Oriented Software Modularization Quality Measurement (International Journal of Engineering and Computer Science, 2014)
Software development and maintenance is major concern to adopting modularization. Measuring the design quality early during software development has been regarded as a prominent way to assure the quality of software products. Several models has been proposed to estimate the quality of software systems.This system proposed an approach for determining the design quality of an Object Oriented software using software metrics. The metrics for object oriented design focus on measurements that are applied to the class and design characteristics. To validate the proposed methodology, we have chosen Open source software project. We extracted a set of chosen software metrics that play a definite role in software design quality. Our metrics characterize the quality of modularization with respect to the APIs of the modules. The percentile average values calculated by these metrics formulate a straight forward approach to assign a design quality for any software systems.For this work simulation, an application is developed in java. This system  examines the modularization quality of OO software by measuring the extent in which a class in a module uses another class in some other module and the extent of inter-module call traffic created by inheritance Experiments are carried out by means of different software version and the result show that it works properly. The outcomes of the experimental study provide a strong base for the effectiveness of our system for metric based design quality measurement of object-oriented software.